(untitled) (Research, Society and Development, 2022)
The objective was to reflect on the use of auriculotherapy as a complementary practice of health care in the context of Primary Care. This is a descriptive study, of a reflective theoretical nature, based on the selection of 23 works. The results were discussed in two thematic blocks: 1) Integrative and Complementary Practices within the SUS and; 2) Integrative and Complementary Practices in the reality of a city in the Zona da Mata Mineira. It is concluded that a connection is possible between the apprehension and application of the National Policy of Integrative and Complementary Practices in the local reality and in the context of Primary Care, by the interdisciplinary health team through the verification of the numerous benefits to the treatment of the patient that can be be achieved from simple and low-cost techniques such as auriculotherapy.